التخدير القطني في جراحة الأطفال "دراسة مقارنة بين التخدير القطني والتخدير الانشاقي" (Latakia University Journal -Medical Sciences Series, 2019)
أجريت الدراسة في مشفى الأسد الجامعي في اللاذقية في قسم التخدير والإنعاش خلال العام (2006 ـ (2005, وقد تضمنت مئة طفل بين (10 ـ (1 سنوات تم تقسيمهم إلى مجموعتين: في المجموعة الأولى فقد تم تطبيق التخدير القطني بالمشاركة مع تركين مناسب لإجراء البزل القطني. أما في المجموعة الثانية فقد تم تطبيق التخدير الانشاقي الكلاسيكي باستخدام غاز الهالوتان. كان التخدير في المجموعة الأولى مريحاً ولطيفاً ومن دون اختلاطات تذكر، باستثناء تحسس وشري بنسبة (2%) وفشل الحصار المطلوب بنسبة (2%). بينما ترافق التخدير في المجموعة الثانية باختلاطات متنوعة: غثيان واقياء بنسبة (4%)، تألم بنسبة (4%)، تشنج حنجرة بنسبة (2%)، تشنج قصبات بنسبة (2%)، اختلاجات بنسبة (6%)، تأخر صحو بنسبة (2%)، تحسس وشري بنسبة (2%)، استنشاق بنسبة (2%)، تهيج وسعال ومقاومة بنسبة (22%)، زيادة مفرزات قصبية بنسبة (10%)، فرط الجرعة بنسبة (2%). وهكذا كانت النتيجة أن التخدير القطني أقل اختلاطات، أقل كلفة، وأقل خطورة من التخدير العام. This study was carried out in the Department of Anaesthesia and Reanimation at ALASSAD University Hospital, Lattakia, during the year (2005 -2006), and included 100 patients between 1 year and 10 years old. They were divided into two groups: 1. In the first group, the spinal anesthesia was applied associated with a suitable sedation to execute the spinal tap. 2. In the second group, inhalation anesthesia by halothane was applied. The anesthesia in first group was kind, comfortable, and without any complications, except sensitiveness and urticaria (2%), and incompetence of the needed block (2%). In the second group, there were many complications: vomiting and nausea (4%), algesia (2%), laryngospasm (2%), bronchospasm (2%), convulsion (2%), delayed recovery(2%), sensitiveness and urticaria (2%), increased the bronchial secretions (10%), hyper dose (2%), cough and excitement and struggling (22%). Therefore, the spinal anesthesia has less complications, less cost, and less risk than inhalation anesthesia by halothane.